Harmonic control in power plant power transformer by means of a built-in passive filter optimized with bacterial foraging algorithm - Yarin Achachagua, Anwar Julio (2021)
Through this research we seek to carry out the study and characterization of a passive harmonic distortion filter applied to the protection of a distribution SS.EE located inside a manufacturing plant. The main purpose is to design the filter based on the internal parameters of the electric transformer, such as its capacitive and inductive reactance, and filter optimization using the particle swarm heuristic method called the bacterial forage algorithm. The passive filter uses the transformer's own capacitance and an external one to tune the rejection band in the frequency range of the harmonic currents. To validate this condition, the CPC 100Omicrom equipment is used, which allows obtaining the tangent delta measurements. In this way, the objective of this built-in passive filter is to achieve adequate and improved working conditions, attending to the needs of protecting both the transformer and the plant machinery to which it supplies, especially in critical circumstances in which the harmonics present in the network are highly aggressive